The Roots of Electronic Jazz, 1950–1970. (1st September 2017) - Holmes, Thom
ABSTRACT: The history of jazz is one of cascading events and styles that continually inform and influence what follows. This transformation is an accumulation over time of styles, methods, and techniques. During the 1950s and 1960s, electronic music gradually left the confines of the institution and migrated into the hands of independent musicians. Among the early explorers were jazz musicians who laid a foundation of experiment for later musicians to model and emulate. This article discusses two types of such experiments: (1) Jazz incorporating prerecorded electronic music on tape (1960–1970) and (2) Jazz using live electronics other than synthesizers (early years from 1965–1970). A discography is provided.